Report of the Behring Sea Commission, 1892 [electronic resource]. - Bering Sea Commission.; Great Britain. Foreign Office. ([London? : s.n.], 1892)
Tables. Cover title. At head of title: Printed for the use of the Foreign Office, June 1892 -Confidential. Electronic reproduction. Mode of access: Internet. 44